Linguistic Tafsir of the Qur'an: Revealing the Theological Dimensions through the Principles of Ism Dhamir in Surah Al Baqarah According to Ibn Athiyyah - Muhammad Syamsul Munir; Khoirul Umami (Penerbit Hellow Pustaka, 2025)
Inaccuracy in understanding the function of dhamir rules in a theological context can lead to incorrect interpretation or neglect of the spiritual dimensions contained in the text. Ibn Athiyyah has a famous work of tafsir by the name of al-Muharrar al-Wajiz fi al-Kitab al-Aziz is one of the books that stands out with linguistics, so it is very detailed in revealing the theological dimensions in the Qur'an through the rules of dhamir in Surah al-Baqarah. . The methodology used in this research is linguistic interpretation with a grammatical and semantic analysis approach based on Ibn Athiyyah's tafsir work. The focus of this research is to reveal the theological dimension in Surah Al-Baqarah through the analysis of linguistic rules, especially the use of Ism Dhamir (pronouns) and Ism Fi'il (verbs) according to Ibn Athiyyah. The results of this study indicate that Ibn Athiyyah utilizes these two rules to clarify and emphasize various theological dimensions, such as tawhid, God's absolute power, and communication between God and His people in Surah al-Baqarah.